Current prevalence and predictors of protein-energy malnutrition among school children in rural Peninsular Malaysia - Al-Mekhlafi, M.S.; Surin, J.; Atiya, A.S.; Ariffin, W.A.; Mahdy, A.K.; Abdullah, H.C. (Seameo Regional Tropical Medicine & Public Health, 2008)
A cross-sectional study was carried out to determine the current prevalence of protein-energy malnutrition (PEM) among Orang Asli schoolchildren and to investigate the potential predictors of malnutrition. A total of 241 (120 males and 121 females) Orang Asli schoolchildren age 7-12 years living in remote areas of Pos Betau, Pahang participated voluntarily in this study. Anthropometric and socioeconomic data were collected and the children were screened for intestinal parasitic infections. The overall prevalences of mild and significant underweight conditions were 52.3 and 37.3, respectively, and the prevalences of mild stunting and wasting were 43.6 and 43.1, respectively, while the prevalences of significant stunting and wasting were 43.6 and 5.6, respectively. There was a significant association between gender (male) and malnutrition (p = 0.029). The results also showed a higher prevalence of stunting among children age < or = 10 years than in older children (p = 0.001). Other independent variables, including socioeconomic status and intestinal parasitic infections, had no significant associations with malnutrition indices. PEM is prevalent among schoolchildren in rural Malaysia and therefore of public health concern since PEM diminishes immune function and impairs cognitive function and educational performance. School-based programs of prevention through health education and interventions should be considered as an essential part of measures to improve the quality of life of schoolchildren in rural Malaysia.